IMPLEMENTASI ALGORITMA APRIORI UNTUK MENENTUKAN STRATEGI PROMOSI SEKOLAH TINGGI SAINS TARBIYAH KOTA PAGAR ALAM - Puspita, Desi; Syahri, Riduan (LPPM UNIVERSITAS BINA INSAN, 2023)
This research aims to implement an a priori algorithm to determine promotion strategies for new students at the Tarbiyah College of Science (STIT) Pagar Alam City. Based on the results of observations and interviews with the committee accepting new students at STIT, the promotion strategy is still carried out thoroughly without looking at target opportunities for places that have potential and those that do not have potential. This is very time-consuming and expensive. The Apriori algorithm is very effective in finding relationship patterns of one or more itemsets in a large data set to determine which study programs are most in demand at the Pagar Alam Tarbiyah College of Science. The process of applying the Apriori algorithm to student data for 2020-2021 uses the Rapidminer application with minimum support of 10% and confidence of 40%, this research obtained information that if the student comes from the PAI study program then comes from the department with a confidence of 44.44%, and if the student comes from SMA N 3 Pagar Alam then comes from the science department with a confidence of 56.09%